2015
DOI: 10.5858/arpa.2013-0754-oa
|View full text |Cite
|
Sign up to set email alerts
|

Conversion, Correction, and International Scale Standardization: Results From a Multicenter External Quality Assessment Study forBCR-ABL1Testing

Abstract: Context.-Monitoring BCR-ABL1 expression levels relative to clinically validated response criteria on the International Scale (IS) is vital in the optimal management of patients with chronic myeloid leukemia, yet significant variability remains across laboratories worldwide.Objective.-To assess method performance, interlaboratory precision, and different IS standardization modalities in representative laboratories performing routine BCR-ABL1 testing.Design.-Fifteen blinded test specimens with 5-level nominal BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The validation and calibration to IS of the ARQ calibrator panels are based on the WHO primary materials, and this international research involving the assessment of linearity, sensitivity, and imprecision demonstrated that the panels enable analytical calibration of local RQ-PCR assay within the context of IS standardization and improve the accuracy and precision of BCR-ABL1 measurement [36]. The panels also have been evaluated in a multicenter external quality assessment study and confirmed that they can facilitate global diffusion of BCR-ABL1 IS standardization in laboratories not yet standardized [37]. The ARQ IS calibrator panels are commercially available and make it easy and convenient to implement IS standardization.…”
Section: Achievements On Bcr-abl1 Standardizationmentioning
confidence: 88%
“…The validation and calibration to IS of the ARQ calibrator panels are based on the WHO primary materials, and this international research involving the assessment of linearity, sensitivity, and imprecision demonstrated that the panels enable analytical calibration of local RQ-PCR assay within the context of IS standardization and improve the accuracy and precision of BCR-ABL1 measurement [36]. The panels also have been evaluated in a multicenter external quality assessment study and confirmed that they can facilitate global diffusion of BCR-ABL1 IS standardization in laboratories not yet standardized [37]. The ARQ IS calibrator panels are commercially available and make it easy and convenient to implement IS standardization.…”
Section: Achievements On Bcr-abl1 Standardizationmentioning
confidence: 88%
“…We eventually selected 22 (out of 29) patients, for which the therapy led to a successful major molecular response (MMR), i.e., the ratio of cells with BCR-ABL mutation is ≤ 0.1 on the international scale (Griffiths et al, 2014).…”
Section: Datasetsmentioning
confidence: 99%
“…We eventually selected 22 (out of 29) patients, for which the therapy led to a successful major molecular response (MMR), i.e., the ratio of cells with BCR-ABL mutation is ≤ 0.1 on the International Scale [54].…”
Section: Datasetsmentioning
confidence: 99%